The implementation of mamdani fuzzy logic in determining student concentration in the computer engineering program - Liku, Antika Diana; Adiba, Fhatiah; Kartika, A.Amalia (Journal of Soft Computing Exploration, 2023)
The selection of a concentration is an important stage for students in the Computer Engineering program at the State University of Makassar before entering the fifth semester. Each student must choose one of the concentrations in the fields of networking, embedded systems, or smart systems. This concentration selection has a significant impact on academic activities and future career abilities. However, the lack of awareness among students about their talents and interests has resulted in many students having difficulty in choosing the right concentration. To address this issue, this research proposes using the Mamdani fuzzy logic method to assist students in selecting the appropriate concentration based on their talents and interests. The approach is carried out by collecting information through questionnaires filled out by students who have completed the fourth semester of the Computer Engineering program. The collected data is then processed using the concepts of Mamdani fuzzy logic in the MATLAB environment to generate concentration scores for each field. The research results show the effectiveness of Mamdani fuzzy logic in determining the concentration of students in networking, embedded systems, and smart systems, with an accuracy rate of up to 80%. By using the appropriate linguistic variables, students' levels of interest and abilities in each field can be accurately represented. This research has benefits for students and the university in identifying the right concentration that aligns with the interests and abilities of students at the State University of Makassar.